RE: Is There a More Practical Way for Screening Minimal Hepatic Encephalopathy? - Deniz Eyice; Ayşe Merve Ok; Abdullah Sonsuz; Mustafa Şükrü Şenocak; Meliha Nur Durak; Sebati Özdemir; Billur Canbakan; Murat Tuncer; Ibrahim Hatemi (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Eyice D, Merve Ok A, Sonsuz A, et al. RE: Is there a more practical way for screening minimal hepatic encephalopathy? Turk J Gastroenterol. 2023;34(6):673.